THE EFFECT OF CERAMIC FIBERS ON THE IMMUNE SYSTEM - Tulinska, Jana; Kuricova, Miroslava; Liskova, Aurelia; Kovacikova, Zuzana; Tatrai, Elizabeth (Biomedical papers, 2005)
Male Sprague-Dawley rats were treated by intratracheal instillation with 1 mg/animal of refractory ceramic fibers. Intratracheal exposure to ceramic fibers led to significant changes of immune response. Results of proliferative activity of spleen lymphocytes showed significantly decreased proliferative activity of T-cells in response to mitogens phytohemagglutinin and concanavalin A in animals given ceramic fibers in comparison with control rats. Similarly, T-dependent B-cell response to pokeweed mitogen was significantly suppressed. Spontaneous proliferative activity of lymphocytes in non-stimulated spleen cell cultures did not differ in exposed and control rats. No significant changes were found among groups in percentage of phagocytic blood polymorphonuclear leukocytes and percentage of cells with respiratory burst.
Keywords: Keywords: Ceramic fibers/Immune system/Immunotoxicity/Lymhpocytes/Phagocytosis/ Immunosuppression